Spontaneous Retropharyngeal Haematoma: Case Report and Literature Overview - Pokharel, Apar; Basnet, Prabhat; Mayya, Naganawalachulu Jayaprakash; Kandel, Damodar (Journal of College of Medical Sciences-Nepal, 2019)
Spontaneous retropharyngeal hematoma is a rare and difficult case to diagnose early. Very few cases have been reported in the literature. We report a rare case of spontaneous retropharyngeal hema-toma presenting with acute onset of neck pain, neck motion limitation and dysphagia. The diagnosis was established by Magnetic Resonance Imaging. The hematoma was drained and the patient condition improved. It is important to be aware of this unusual condition with its distinct presentation. Most cases will resolve with conservative management. Surgical intervention is needed if medical management fails.